Addressing the Gap: Accountability Mechanisms for Peacekeepers Accused of Sexual Exploitation and Abuse - van Leeuwen, Jayden (Victoria University of Wellington Law Review, 2019)
The United Nations (UN) has been plagued by incidents of sexual exploitation and abuse by peacekeepers for a number of years. These tragedies have had major implications for the credibility of the organisation and have hindered its ability to achieve its goals. As the organisation has struggled to address this problem, a new form of accountability has evolved: direct non-legal accountability. This article examines the problem of sexual exploitation and abuse by peacekeepers, previous responses to this problem and the emergence of this new type of accountability. Direct non-legal accountability provides a viable alternative to standard conceptions of accountability in response to the situation. Although it will not solve the problem of sexual exploitation and abuse, normative improvements could be made to these mechanisms in order to better provide some accountability to the victims of this exploitation and abuse.